The Use of Papaya Seeds (Carica papaya L.) as a Biocoagulant in the Dairy Industry Liquid Waste Treatment Process with the Coagulation-Flocculation Method - Riananda, Zavira; Wirosoedarmo, Ruslan; Suharto, Bambang (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Dairy industry discharges wastewater characterized by high values of Total Suspended Solid and turbidity. The waste is commonly processed using chemical coagulants which negatively impact humans health and the environment. Papaya seeds can be used as a coagulant as their positively charged proteins that can bind the negatively charged particles allowing the resulting floc to settle and clear water to be obtained. The goals of this study are to determine the characteristics of the dairy industry wastewater before and after flocculation coagulation, the characteristics papaya seed biocoagulant, the effect of the biocoagulants dosses, particle sizes, and stirring speed on the turbidity and the Total Suspended Solid of the dairy industry wastewater, and the performance of the biocoagulants in processing the dairy industry waste using Sludge Volume Index and Sludge Mass. The treatments applied in this research are in terms of doses (250 mg, 500 mg, and 750 mg), particle sizes (60,120, and 230 mesh), fast stirring speeds (120 rpm, 180rpm, 200 rpm for 1 minute), and slow stirring speeds (10 rpm, 30rpm, and 50 rpm for 20 minutes) all of which were expected to reduce the wastes turbidity and the number of Total Suspended Solid. This study finds that the treatment with the highest reduction of Total Suspended Solid is D3P3KP2, which decreased turbidity from 754 NTU to 92 NTU. The treatment with the highest reduction of Total Suspended Solid was D3P3KP2 which decrease the Total Suspended Solid from 124 mg/L to 79 mg/L. The performance of the papaya seed biocoagulant of D3P3KP2 treatment is considered good as the acquired highest value of the Sludge Volume Index is 83.13 ml/g and as the procured lowest value of the Sludge Mass is 81.48%.